Biological value of tomato processing by-products - Benderska (Dushchak), Olga; Bessarab, Alexander; Shutyuk, Vitaliy; Iegorov, Bogdan; Kashkano, Mariana (My University, 2021)
The article analyzes the biological value of secondary products of tomato processing, namely tomato seeds, which, for the most part, is not considered as an object of processing. The use of secondary raw materials formed in the production of tomato products as a source of biologically active substances with their subsequent use in food technology is proposed. The results of theoretical and experimental studies of the biological value of tomato seeds. It has been found that tomato seeds have a high nutritional and biological value due to the high concentration of proteins, lipids, and carbohydrates. У статті проведено аналіз біологічної цінності вторинних продуктів томатопереробки, а саме томатного насіння, що, здебільшого не розглядається в харчовій промисловості як об’єкт перероблення. Запропоновано застосування вторинної сировини, що утворюється при виробництві томатопродуктів – томатного насіння, – як джерела отримання біологічно активних речовин з подальшим їх використанням в технологіях харчових продуктів. Наведено результати теоретичних та експериментальних досліджень фізико-хімічного складу томатного насіння.
Keywords: tomatoes; proteinases; seeds; inactivation; trypsin; томати; протеїнази; насіння; інактивація; трипсин; кафедра технології консервування